Development of improved reinforcement learning smart charging strategy for electric vehicle fleet. (1st August 2023) - Sultanuddin, S.J.; Vibin, R.; Rajesh Kumar, A.; Behera, Nihar Ranjan; Pasha, M. Jahir; Baseer, K.K.
Abstract: Due to its environmental and energy sustainability, electric vehicles (EV) have emerged as the preferred option in the current transportation system. Uncontrolled EV charging, however, can raise consumers; charging costs and overwhelm the grid. Smart charging coordination systems are required to prevent the grid overload caused by charging too many electric vehicles at once. In light of the baseload that is present in the power grid, this research suggests an improved reinforcement learning charging management system. An optimization method, however, requires some knowledge in advance, such as the time the vehicle departs and how much energy it will need when it arrives at the charging station. Therefore, under realistic operating conditions, our improved Reinforcement Learning method with Double Deep Q-learning approach provides an adjustable, scalable, and flexible strategy for an electric car fleet. Our proposed approach provides fair value which solves the overestimation action value problem in deep Q-learning. Then, a number of different charging strategies are compared to the Reinforcement Learning algorithm. The proposed Reinforcement Learning technique minimizes the variance of the overall load by 68 % when compared to an uncontrolled charging strategy.